2002
DOI: 10.1002/cncr.10245
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue in cancer patients compared with fatigue in the general United States population

Abstract: Melnick‐Needles syndrome is a rare putative X‐linked dominant bone dysplasia. The patients have short stature, characteristic facial features, and a normal intelligence. The skeletal dysplasia includes S‐shaped curvature of tubular bones and sclerosis of the base of the skull. The phenotype of affected individuals varies, even within families. This could be related to X chromosome inactivation. We report here on a very mildly affected mother and her two severely affected daughters with characteristic features … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

32
547
8
10

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 698 publications
(597 citation statements)
references
References 40 publications
32
547
8
10
Order By: Relevance
“…Moreover, previous studies have confirmed that breast cancer survivors with increased fatigue rated their quality of life at a lower level [12][13][14]16 . On the other hand, assessing fatigue in cancer survivors is a challenge since fatigue is also a common complaint with some level of fatigue reported by the general population 17,18 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, previous studies have confirmed that breast cancer survivors with increased fatigue rated their quality of life at a lower level [12][13][14]16 . On the other hand, assessing fatigue in cancer survivors is a challenge since fatigue is also a common complaint with some level of fatigue reported by the general population 17,18 .…”
Section: Introductionmentioning
confidence: 99%
“…Third, a nurse evaluated symptomatology frequently experienced as late-onset physical sequelae of gynecologic cancer treatment-bladder, urinary tract, bowel, and endocrine changes/dysfunction (Janda, Obermair, Cella, Crandon, & Trimmel, 2004). We also included patient-reported posttreatment vaginal changes and fatigue, which are common, significantly affect quality of life (Broeckel, Jacobsen, Horton, Balducci, & Lyman, 1998;Cella, Lai, Chang, Peterman, & Slavin, 2002), and are associated with lower frequency of sexual activity (Cain et al, 2003). Finally, we assessed, from the participant's perspective, her partner's sexual difficulties to control for relative access to a sexual partner, as men with sexual dysfunction are significantly less likely to be sexually active (Blanker et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Physical, cancer-or treatment-related factors such as anemia [7], receiving chemotherapy [16], radiotherapy [25], and/or hormone therapy only partially explain the difference with fatigue in the general population. Regarding the association between fatigue and personality in (breast) cancer patients, inconsistent findings were reported.…”
Section: Introductionmentioning
confidence: 99%